Hardiness Behavior and Organizational Loyalty of Government Secondary School Teachers in Palestine - Ghassan H. Hilo (Sultan Qaboos University, 2009)
The purpose of this study was to a) investigate hardiness behavior and organizational loyalty levels among secondary school teachers in the northern districts of the West Bank in Palestine and b) determine the effect of teachers' gender and years of experience. The sample consisted of 396 male and female secondary school teachers, which were selected randomly from the target population. The questionnaire used in the study contained 42 items on hardiness behavior domain and 28 items for organizational loyalty domain. The results indicated that there was a moderate level of hardiness behavior among teachers (68.6%). Also, the results revealed that there were statistically significant differences due to gender and years of experience in commitment and participation items in favor of longer teaching experience. There were also statistically significant differences due to gender, and interaction between gender and years of experience, in control items in favor of males with longer teaching experience. There were significant differences due to years of experience, and interaction between gender and years of experience in the overall degree of hardiness behavior, in favor of longer teaching experience. There were significant differences due to gender and years of experience in the overall degree of organizational loyalty domain in favor of females with longer teaching experience. The researcher recommended the reinforcement of hardiness behavior and organizational loyalty levels among Palestinian teachers.